Graves’ disease as a driver of depression: a mechanistic insight - Song, Yifei; Wang, Xinying; Ma, Wenxin; Yang, Yan; Yan, Shuxin; Sun, Jiapan; Zhu, Xiaoyun; Tang, Yang (Frontiers in Endocrinology, 2023)
Graves’ disease (GD) is characterized by diffuse enlargement and overactivity of the thyroid gland, which may be accompanied by other physical symptoms. Among them, depression can dramatically damage patients’ quality of life, yet its prevalence in GD has not received adequate attention. Some studies have established a strong correlation between GD and increased risk of depression, though the sample sizes in most studies remain small. The summary of mechanistic insights regarding GD and depression has underpinned possible pathways by which GD increases the incidence of depression. In this review, we first summarized the clinical evidence that supported the increased prevalence of depression by GD. We then concentrated on the mechanistic findings related to the acceleration of depression in the context of GD, as mounting evidence has indicated that GD promotes the development of depression through a variety of mechanisms, including triggering autoimmune responses, inducing hormonal disorders, and influencing the thyroid-gut-microbiome-brain axis. Finally, we briefly address potential therapeutic approaches to decreasing the risk of depression among patients with GD.